RATE OF THE QUANTITY OF MATERIAL RECOVERY FACILITIES INCREASE IN UKRAINE - Bereziuk, Oleg; Kraevskyi, Volodymyr (Scientific Works of Vinnytsia National Technical University, 2022)
Sorting of the solid municipal waste promotes the extension and reuse of the waste. Sorting and preparation for further recycling, disinfection and disposal of non-toxic solid municipal waste, collected by indiscriminative method, is performed by material recovery facilities. Determination of the regressive dependence, that describes the rate of material recovery facilities increase in Ukraine is urgent scientific-engineering problem. The aim of the study is determination of the regressive dependence, describing the rate of these facilities growth and can be used for the prediction of the quantity of such facilities. In the process of the study the method of regressive analysis of the results of single-factor experiments and other pair dependences with the selection of the rational type of function from the sixteen most widespread variants by the criterion of the maximum value of the correlation coefficient has been used. Regression was carried out on the base of the linearized transforms, which enable to reduce non-linear dependence to linear one. Determination of the beta coefficients was carried out applying the least square method, by means of the elaborated computer program "RegAnaliz", protected by the Certificate of the State Rregistration of the rights to the copyright object. Adequate regression exponential function, describing the rate of the material recovery facilities increase in Ukraine and can be used for the prediction of the number of such facilities has been obtained. Graphic dependence, that describes the rate of the number of material recovery facilities increase in Ukraine and allows to illustrate this dynamics, show sufficient reproducibility of the theoretical results with factual data has been constructed. Using the obtained dependence it is estimated that for the sorting of the annual volume of SMW in Ukraine the necessary quantity of material recovery facilities at the present rate of increase can be provided by 2040.